Development of corporate social responsibility in small and medium-sized enterprises and its nexus with quality management - Manuel Larrán Jorge; Jesús Herrera Madue\~no; María Paula Lechuga Sancho; Domingo Martínez-Martínez (Cogent Business & Management, 2016)
The role and impact of small and medium enterprises (SMEs) in the economy means that it is becoming increasingly difficult to dismiss the importance of the latter in socially relevant issues as important as employment, innovation and standard of living. Through content analysis, this study mainly provides a literature survey about the concept of Corporate Social Responsibility (CSR) in relation to quality management in SMEs. It seeks to identify main CSR practices SMEs develop, and investigate if they are related to quality management practices directly or at least implicitly. This would help us to identify parallels between quality management and the importance of conducting socially responsible management. Using 107 empirical studies from 1976 to September 2014, this study provides a baseline for future empirical studies in these areas. For this purpose, main topics and practices of CSR in the SME context are identified. Specifically, we arrive at the conclusion that these firms are increasingly integrating both CSR and quality management practices to comply with stakeholders needs, and that most common social and environmental practices facilitate the development of quality management practices.
Keywords: 650